2003
DOI: 10.1088/0022-3727/36/8/313
|View full text |Cite
|
Sign up to set email alerts
|

Structural and mechanical properties of chromium nitride, molybdenum nitride, and tungsten nitride thin films

Abstract: Cr-N, Mo-N, and W-N thin films are deposited on silicon by rf reactive magnetron sputtering. The crystallographic phase and residual stress are determined by x-ray diffraction analysis. In each of the three material systems, a hexagonal and a face-centred cubic (fcc) phase are observed. Plasma diagnostics using energy-resolved mass spectroscopy reveal that a significant fraction of the Cr + ions exhibits a high flux and kinetic energy if the nitrogen partial pressure p N 2 is low. These high-energy ions effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(94 citation statements)
references
References 44 publications
8
85
1
Order By: Relevance
“…The hardness of δ-MoN is similar to the one measured for γ-Mo2N [30], whereas the elastic modulus is somewhat higher (Table 3). In contrast with γ-Mo2N, compressive stresses are measured for the hexagonal phase.…”
Section: Stoichiometric δ-Mon and Cubic Mon Phasessupporting
confidence: 75%
See 2 more Smart Citations
“…The hardness of δ-MoN is similar to the one measured for γ-Mo2N [30], whereas the elastic modulus is somewhat higher (Table 3). In contrast with γ-Mo2N, compressive stresses are measured for the hexagonal phase.…”
Section: Stoichiometric δ-Mon and Cubic Mon Phasessupporting
confidence: 75%
“…Hones et al [30] used the same process as [29] to investigate the structural and mechanical properties of molybdenum nitride films about 1 μm thick in a wide range of nitrogen/metal ratios. The discharge power is kept constant at 120 W, the total pressure of (Ar-N2) gas mixture during the sputtering process is equal to 0.66 Pa and the substrate temperature is fixed at 500 ± 20 K in order to obtain films of structures in the zone T regime of Thornton's structure zone classification which allows optimizing the mechanical properties of films (Section 5).…”
Section: Influence Of the Nitrogen Pressure On The Formation Of Mon Pmentioning
confidence: 99%
See 1 more Smart Citation
“…According to former research for CrN x deposition by reactive magnetron sputtering, different phases such as Cr, Cr þ N, Cr þ N þ Cr 2 N, Cr 2 N þ CrN, CrN can be obtained depending on nitrogen content. [18][19][20][21] In this study, an fcc-CrN phase has formed at lower pulse widths while a mixed structure of hcpAlN, hcp-Cr 2 N and a small amount of fcc-CrN phases exists in the films at higher pulse widths. Lin et al demonstrated that the maximum N þ ion energy increased with a decrease of pulse width (increasing the duty cycle) at lower frequencies below 300 kHz in the Pulsed Closed Field Unbalanced Magnetron Sputtering system.…”
Section: Discussionmentioning
confidence: 99%
“…Other examples of transversely isotropic material with a pronounced columnar microstructure are CrN, Cr 2 N, MoN, and WN nitride thin films, deposited on silicon substrate, see Hones et al [25], or tool steel W300, to form protection coating against wear and oxidation. By use of scanning electron microscopy, various composition of nitrides have been examined, but in pure CrN films the pronounced columnar nanotexture was observed.…”
Section: Fabricationmentioning
confidence: 99%